Alphas Storytelling: Mapping Childrenswear Possible Worlds, Defining Seasonal Brands Territories - Simona Ironico (ZoneModa Journal, 2018)
Born from 2010 and raised by Millennials, Alphas represent today the youngest generational market segment. Raising as “screenagers” in mostly only-child family environments, technology is shaping their present and future consumer culture. In this scenario, contemporary trends such as hyper individualism, instant gratification, gamification, gender fluidity, slow play, sustainability and reconnection with nature are destined to reach their apotheosis. The paper adopts the socio-semiotic interpretative framework of “Possible Worlds” to map the rich set of narratives generated by childrenswear collections and communication strategies. Comparing inspirations and aesthetics, four storytelling approaches will be discussed: Down to Earth (Plausible Worlds), Imagination Driven (Implausible Worlds), Conceptual (Impossible Worlds) and Surreal (Unconceivable Worlds). In addition to reveal contemporary trends and seasonal brand territories, the analysis of kidswear “fashion tales” will enable to get important insights about Alphas unripe consumer culture.